Molecular epidemiology is becoming complex under the dynamic HIV prevalence: The perspective from Harbin, China - Shao, Bing; Song, Bo; Cao, Lijun; Du, Juan; Sun, Dongying; Lin, Yuanlong; Wang, Binyou; Wang, Fuxiang; Wang, Sunran (Journal of medical virology, 2016)
Unlike most areas of China, HIV transmission via men who have sex with men (MSM) is increasing rapidly, and has become the main route of HIV transmission in Harbin city. The purpose of the current study was to elaborate the molecular epidemiologic characteristics of the new HIV epidemic. Eighty‐one HIV‐1 gag gene sequences (HXB2:806–1861) from local HIV infections were isolated; CRF01_AE predominated among HIV infections (71.6%), followed by subtype B (16.5%), CRF07_BC (6.2%), and unique recombinant strains (URFs; 6.2%). URFs were most often identified in the MSM population, which consisted of a recombination of CRF01_AE with subtype B or CRF07_BC. Six clusters were formed in this analysis; clusters I and II mainly circulated in southwest China. Clusters III and IV mainly circulated in southwest, southeast, and central China. Clusters V and VI mainly circulated in north and northeast China. Clusters III and IV may facilitate the transmission of the CRF01_AE strain from the southwest to the north and northeast regions of China. HIV subtypes are becoming diverse with the persistent epidemic in this geographic region. In brief, our results indicate that the molecular epidemiology of HIV is trending to be more complex. Thus, timely molecular epidemiologic supervision of HIV is necessary, especially for the MSM population. J. Med. Virol. 88:807–814, 2016. © 2015 Wiley Periodicals, Inc.